Pengaruh Kualitas Pelayanan, Harga dan Kepercayaan Terhadap Kepuasan Pelanggan di CV. Indo Jaya Putra Surabaya - Widyana, Widyana; Pradiani, Theresia; Fatorrahman, Fatorrahman (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study aims to analyze the effect of service quality, price, and trust on customer satisfaction at CV. Indo Jaya Putra Surabaya. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to customers of CV. Indo Jaya Putra, then analyzed using multiple linear regression to determine the relationship and influence of each independent variable on customer satisfaction. The results of the study indicate that service quality, price, and trust have a significant effect both partially and simultaneously on customer satisfaction. This is evidenced by the partial significance value for the service quality variable of 0.039 <0.05. For the price variable, the significance value is 0.000 <0.05 and for the trust variable, the significance value is 0.012 <0.05.